The main characteristics of the notary system of Turkey (Journal of actual problems of jurisprudence, 2022)
In Turkey, the notary is a public (state) service. But nevertheless, the notary has a unique status. On the one hand, although notaries by some parameters belong to civil servants, on the other hand, they are self-employed, have the right to hire and dismiss an employee, dispose of the income received, appear in court on their own behalf, pay taxes independently. At the same time, notary expenses are not covered by the state.The onset of the responsibility of the notary of Turkey according to Article 162 of the Law on the Notary is not tied to the fault. Even if it was done by interns, secretaries and candidates for secretaries, notaries are responsible for those who suffered because the work was not done or was done incorrectly or incompletely. Here it turns out that the conditions of the notary's responsibility are the illegal notarial activity of the notary or his trainees, the secretary and the candidate for secretaries and the causal relationship between illegal notarial activity and harm. Liability disappears only if the notary proves that there is no causal relationship between the notary's notarial activity and the damage that has occurred. The article describes the main characteristics of the notary system of Turkey. In Turkey, notaries play an important role in the legal system. The function of notaries is to certify documents that are indisputable evidence. That is, until proven otherwise, notarized documents are indisputable evidence.Keywords: notary-notary-notary status-uniqueness of notary status, notary's responsibility, notary's innocent responsibility.